Barriers to Intercultural Communication of Papuan Ethnic Students in Social Interaction at Ichsan University, Gorontalo - Minarni Tolapa; Andi Subhan; Dwi Ratnasari (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study aims to identify the intercultural communication barriers faced by Papuan ethnic students in their social interactions at Ichsan University Gorontalo. The method used in this study is a qualitative research method, with data analysis techniques employing the interactive model of Miles and Huberman. The findings show that there are several intercultural communication barriers experienced by Papuan ethnic students in their social interactions within the environment of Ichsan University Gorontalo. These barriers include the assumption of similarity, which views all cultures as being the same and thus leads to misunderstandings; barriers caused by language differences during communication; barriers resulting from misinterpretation of non-verbal messages such as gestures, body language, and facial expressions; barriers caused by stereotypes and prejudices, especially those of a negative nature during interactions; barriers stemming from a tendency to make negative judgments; and barriers due to deep anxiety and apprehension before engaging in a communication process during interactions.